By the shores of Silver Lake - Wilder, Laura Ingalls, 1867-1957.; Williams, Garth (New York, Harper, 1953)
Ma and the girls follow Pa west by train where they make their home at a rough railroad camp and plan for their own homestead.
Children's Catalog (Wilson)
Elementary School Library Collection (Bro-Dart)
Booklist
5.5
3-6
Keywords: Frontier and pioneer life -- Fiction; Family life -- Fiction; Frontier and pioneer life -- Fiction